Brassinosteroid signals cooperate with katanin‐mediated microtubule severing to control stamen filament elongation. (22nd December 2022) - Wang, Jie; Wang, Guangda; Liu, Weiwei; Yang, Huanhuan; Wang, Chaofeng; Chen, Weiyue; Zhang, Xiaxia; Tian, Juan; Yu, Yanjun; Li, Jia; Xue, Yongbiao; Kong, Zhaosheng
Abstract: Proper stamen filament elongation is essential for pollination and plant reproduction. Plant hormones are extensively involved in every stage of stamen development; however, the cellular mechanisms by which phytohormone signals couple with microtubule dynamics to control filament elongation remain unclear. Here, we screened a series of Arabidopsis thaliana mutants showing different microtubule defects and revealed that only those unable to sever microtubules, lue1 and ktn80.1234, displayed differential floral organ elongation with less elongated stamen filaments. Prompted by short stamen filaments and severe decrease in KTN1 and KTN80s expression in qui‐2 lacking five BZR1‐family transcription factors (BFTFs), we investigated the crosstalk between microtubule severing and brassinosteroid (BR) signaling. The BFTFs transcriptionally activate katanin‐encoding genes, and the microtubule‐severing frequency was severely reduced in qui‐2 . Taken together, our findings reveal how BRs can regulate cytoskeletal dynamics to coordinate the proper development of reproductive organs. Synopsis: Stamen elongation is required for successful pollination and reproduction in plants. Here, brassinosteroid‐activated BZR1‐family transcription factors (BFTFs) are shown to control stamen filament elongation via promotion of katanin‐mediated microtubule‐severing. Mutations in genes encoding regulators of microtubule severing lead to defects in stamen filament elongation. Loss of katanin function or a deletion of all five BFTFs impairs cell elongation in stamen filaments. Brassinosteroid treatment or BFTF activation induces transcription of katanin‐encoding genes. Abstract : BZR1‐family transcription factors induce cell elongation in stamen filaments in Arabidopsis thaliana via activation of katanin expression.